(untitled) (Research, Society and Development, 2022)
The present study aimed to analyze what postgraduate studies in Physical Education in Brazil have produced on pedagogical practices with theater and storytelling in Early Childhood Education. This was bibliographic research, carried out in the Capes Theses and Dissertations Catalog and the Brazilian Digital Library of Theses and Dissertations. The study corpus consists of 58 works (51 dissertations and seven theses). In the process of data analysis, bibliometric indicators and thematic analysis were mobilized. In the thematic dimension, the results found were grouped into six analytical categories: 1) child protagonism; 2) pedagogical mediation; 3) teacher training; 4) theoretical discussion; 5) motor development; 6) inclusion and routine. The results indicate an increase in production from 2007, which may be related to the increase in the number of graduate programs in Physical Education and the achievements in the field of public policies for children. Despite being recognized as potent languages ​​in Early Childhood Education, storytelling and theater appear peripherally in most of the works analyzed. There is little emphasis on the didactic-methodological dimension of dealing with these languages ​​and little visibility for children’s authorial productions and practices about this knowledge.